Repaired Reinforced Concrete Beams with Normal and High Strength Concrete - Emad Yassin Khudhair (Diyala Journal of Engineering Sciences, 2013)
In resent years several attempts were undertaken to repair damaged reinforced concrete structures. Studies on the effectiveness of repaired and strengthened reinforced concrete elements which fail primarily due to formation of major flexural cracks are same what limited for normal strength concrete (NSC) and very limited for high strength concrete (HSC). The overall objective of the present work is to investigate the strength and deformation characteristics in flexure of reinforced HSC and NSC beams repaired with either with concrete alone or with fiber reinforced concrete or with Welded Wire Mesh (W.W.M). From the results obtained, it was found that the beams were adequately repaired and the general mode of failure was flexural. The repaired beams had higher strength than the original beams. All repaired beams exhibited significant decrease in deflection than the original beams.